2014
DOI: 10.1007/s10815-014-0409-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of Wnt signaling members in the uterus and embryo during pre-implantation and implantation

Abstract: Wnt family members are best known for their roles in cell fate determination, differentiation, proliferation and apoptosis during embryonic development. Wnt signaling becomes effective during these cellular processes through the proper interaction between its ligands, receptors, effectors and inhibitors. Here we review Wnt signaling in terms of embryonic development to the blastocyst stage implantation with emphasis on endometrial changes that are critical for receptivity in the uterus. The relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 86 publications
0
71
0
Order By: Relevance
“…The WNT signaling pathway is involved in several BPs such as embryonic induction, generation of cell polarity and specification of cell fate (Cadigan & Nusse, ), and embryo‐uterine crosstalk during the embryo implantation stage (Biase et al, ; Chen et al, ; Tepekoy, Akkoyunlu, & Demir, ). We found that blastocysts of both groups expressed at least 16 WNT ligand genes, with greatest read number for WNT6, WNT7A, WNT11, WNT2B , and WNT5B .…”
Section: Discussionmentioning
confidence: 99%
“…The WNT signaling pathway is involved in several BPs such as embryonic induction, generation of cell polarity and specification of cell fate (Cadigan & Nusse, ), and embryo‐uterine crosstalk during the embryo implantation stage (Biase et al, ; Chen et al, ; Tepekoy, Akkoyunlu, & Demir, ). We found that blastocysts of both groups expressed at least 16 WNT ligand genes, with greatest read number for WNT6, WNT7A, WNT11, WNT2B , and WNT5B .…”
Section: Discussionmentioning
confidence: 99%
“…Wnt family members are expressed in the reproductive tract, especially Wnt4, Wnt5a and WNT7a (associated with the altered miRNA in our study) (Hayashi et al 2011, Tepekoy et al 2014). Furthermore, endometrial receptivity seems to be regulated by the Wnt pathway (Tepekoy et al 2014), as Wnt7a, Wnt3, Wnt3a and Wnt1 have been associated with essential peri-implantation endometrial changes in humans and mammals (Chen et al 2009, Sonderegger et al 2010, Tsang et al 2012, Tepekoy et al 2014, Goad et al 2017.…”
Section: Discussionmentioning
confidence: 49%
“…Therefore, we tried to identify the complete miRNA profile that is influenced by the ART outcome in order to correlate this profile with the pathway most likely targeted. By using the 11 miRNAs with the highest significant alterations in our analysis, we discovered that they were all associated with the regulation of WNT 3 and WNT7a, essential proteins of the Wnt pathway, that was recently described as critical for early embryonic development, as well as for the luteal transformation of the endometrium (Chen et al 2009, Sonderegger et al 2010, Tepekoy et al 2014). This pathway consists of different proteins playing an important role in cell differentiation, apoptosis, proliferation and determination of cell fate (Tepekoy et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decidualization is one of the most important post‐implantation events that support embryonic development and provide nutrients until a functional placenta is formed (50, 51). Primarily induced by P4, endometrial stromal cells differentiate into secretory decidual cells at the time of blastocyst attachment to the uterine epithelium (52).…”
Section: Involvement Of Sgk1 In Decidualizationmentioning
confidence: 99%